Conference Report: 17th Annual Meeting of the German Society for Gene Therapy. (January 2011) - Büning, Hildegard; Baum, Christopher; Ehrhardt, Anja; Nettelbeck, Dirk M; Ogris, Manfred
The 17th Annual Meeting of the German Society for Gene Therapy was held at the Chemistry and Pharmacy Campus of the University of Munich in conjunction with and supported by the British Society for Gene Therapy, the Viral Vectors Study Group of the German Society for Virology, the Research Priority Program SPP1230, the Nanosystems Initiative Munich and the Helmholtz Center Munich. The German Research Foundation provided financial support for the invited international speakers. In addition to 25 invited lectures, 21 oral presentations were selected out of more than 100 submitted abstracts. State-of-the-art advances in the field of gene therapy were presented, a field that has considerably evolved within recent years. More than 200 researchers from Germany and other European countries, as well as the USA, Canada and Japan attended the meeting. Prior to the official meeting, a public day was organized, in which the interested public could participate in talks and discussions concerning gene therapy issues. Furthermore, at the 'kids workshop' young scientists aged 8–10 years were discovering cellular and genetic mechanisms and the principles of gene therapy.